Evalution of efficiency of Verticillium lecanii and Beauveria bassiana to control Agrotis oipsillia - H. M. Saleh; F. H. Aboud; N. Kh. Mousa; F. H. Said (Journal of Madenat Alelem University College, 2010)
This study conducted to evaluate efficiency of two entomopathogenic fungi and their combination as bioagents cotton leave worm (Agrotis oipsillia) under lab. and field condition. Two methods were followed for insect treatment by addition spore suspension with irrigated water and using feeding bits(107 spore /ml)"both fungi carried by corn bean". The result showed that any fungus, either individually or combination increasing the percent mortality of insect compared with control .The use of method after mixing the two fungi was superior for insect mortality (98%) as compared to use the spore suspention (69.8% and 58%) under lab. And field conditions respectively after 7 days of treatment